تنظيـــم الاجتماعـــات في المشـــاريع الإنشـــائية - صــالح مجـــول هـــادي (Journal of Engineering and Sustainable Development, 2008)
The construction project is considered one of the most important sciences, it progressed greatly for what include of science, art, and experience, it is very important now to finish the project in the exact time, decided cost and required quality which can be obtained by many ways, the most important one is holding or organizing meetings in the projects, by this way the organized work between the project members will be accomplished through being responsible into consideration in order to achieve their duties. In this research, the most important reasons that lead to the failure of the projects in construction projects by using a questionnaire list and personal interviews and field visits done by the researcher to the projects to know the situation of projects organizing in the construction projects in the present, which do not follow the decisions taken in the meeting and take an extra time which is not important and does not accomplish the desired benefits in addition to the shortage of discipline in the needing time more than what is the plant for and many other reasons that are being pointed to in questionnaire list. As result, the researcher makes suggestions to organize meetings in the construction projects in an idealized way through knowing what should be done before and during, and after holding meetings, in addition, to knowing the most important requirements to make the meetings succeed...